PELATIHAN MENGELOLA DATA MENGGUNAKAN APLIKASI SPSS KEPADA MAHASISWA DI RIAU - Kurniati, Annisah; Rahmi, Depriwana; Yuniati, Suci (Universitas Mataram, 2025)
Many undergraduate students continue to encounter challenges in mastering statistical data analysis using SPSS, a skill that is essential for conducting research and completing undergraduate theses involving statistical tests. In practice, it is still common for students to rely on third-party services to perform data analysis—an issue that raises concerns regarding academic integrity and highlights a lack of essential research competencies. This study aimed to design and implement a structured SPSS training program for 83 fourth-semester students from various study programs within the Faculty of Tarbiyah and Teacher Training at UIN Suska Riau. The training was developed through a series of systematic phases, including a preliminary needs assessment, SPSS installation, direct instruction, interactive discussions with guided scaffolding, and report writing. The findings indicated a high level of participant engagement throughout the training. More importantly, the program led to a significant improvement in students’ understanding and ability to perform statistical data analysis using SPSS. The results demonstrate that structured training interventions can have a substantial impact on enhancing students’ research competencies and promoting data-informed academic practices. This initiative contributes meaningfully to improving the quality of student research and fostering a stronger research culture within the faculty.